Media Pembelajaran Aksara Sunda Menggunakan Augmented Reality Berbasis Android - Ahmad A Hidayat; Ade Sutedi; Erwin Gunadhi (Institut Teknologi Garut, 2022)
Sundanese script learning media is a learning system with android-based mobile technology that is used as a supporting medium for learning Sundanese script. The learning process in schools generally still uses books, so alternative media are needed that can attract students' attention in learning writing, letters, and forms of the Sundanese script. In this research, Sundanese script learning media was developed using Augmented Reality as a support for the learning process for class VII junior high school which can be run on Android-based devices. The development methodology in this research is the Multimedia Development Life Cycle which includes the stages of Concept, Design, Material Collecting, Assembly, Testing, and Distribution. The results of this study are in the form of learning media applications to learn how to write and pronounce Sundanese script accompanied by Augmented Reality (3D) forms accompanied by videos. In addition, based on the survey results obtained 93.6% indicating that the use of the Sundanese Script Learning Media application using Android-Based Augmented Reality can support the learning of the Sundanese Script properly.